AB0549 Patients with Long-Standing Primary Antiphospholipid Syndrome: Retrospective Analysis of Recurrences, Organ Damage and Mortality. (10th June 2014) - Reggia, R.; Taraborelli, M.; Dall'Ara, F.; Andreoli, L.; Frassi, M.; Taglietti, M.; Franceschini, F.; Tincani, A.
Abstract : Background: While acute manifestations related to APS are well known and their treatment is quite standardized, informations on the long-term outcome in affected patients are still very limited 1–3, even though the disease has been known for at least 30 years. Objectives: Primary objective was to assess the prevalence of thrombotic and obstetrical recurrences, severe complications, organ damage (and related risk factors) and mortality in PAPS with long-standing disease. We also compared systemic involvement, serological alterations, cardiovascular risk factors and therapy between the onset and the follow-up. Methods: Medical records of patients with PAPS regularly and prospectively followed in our center for at least 15 years were retrospectively reviewed. Fisher's exact test for categorical variables was used. P values <0.05 were considered significant. Results: Thirty-five Caucasian patients (33 female and 2 male) with diagnosis of PAPS (Miyakis et al 2006) followed from 1984 to 2013 with a mean age at onset of 32 years (SD 8.17) and a median follow-up of 20.5 years (range 15-30) were included in this analysis. A thrombotic event appeared in 28% of patients during follow up (venous in 50%, arterial in 40% and both in 10%). Nineteen patients (57%) had a total of 28 pregnancies, that was successful in 75% of cases. No CAPS were observed during follow-up. Hemorrhagic, infective, neoplastic events were recorded in 34%, 6% and 9% of patients respectively. Organ damage was present in 20% of patients at the end of follow-up (17% neurological deficit and 3% chronic kidney failure)and was statistically significantly associated to a previous thrombotic history (p:0.027) and in particular to a previous arterial thrombosis (p<0.001). One patient (3%) died for sepsis due to chronic bowel ischemia. No statistically significant variations were observed between the onset and follow-up for systemic involvement, serological alterations but for cardiovascular risk factors (less estroprogestinic use p: 0.002) and therapy (more Hydroxicloroquine p<0.001; more Immunosuppressant p: 0.055; more anti-hypertensive p:0.006). Conclusions: Despite therapy, a high proportion of patients experiences new thrombotic events and severe complications, while pregnancy outcome seems to be quite good. Organ damage progresses in a significant proportion of patients and it is associated with previous arterial events. Unluckily PAPS can be mortal. A strict control of cardiovascular risk factors and effective treatment are needed to improve the long term outcome. References: Erkan D, Yazici Y, Sobel R, Lockshin MD. Primary antiphospholipid syndrome: functional outcome after 10 years. J Rheumatol. 2000;27:2817-21 Cervera R, Khamashta MA, Shoenfeld Y, Camps MT, Jacobsen S, Kiss E, et al. Morbidity and mortality in the Antiphospholipid syndrome during a 5-year period: A multicenter prospective study of 1000 patients. Ann Rheum Dis 2009;68:1428-32 Grika EP, Ziakas PD, Zintzaras E, Moutsopoulos HM, Vlachoyiannopoulos PG. Morbidity, mortality, and organ damage in patients with Antiphospholipid syndrome. J Rheumatol. 2012; 39:516-23. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1759